Ozoniotherapy as a coadjuvant in the irrigation of the radicular channels system - Fernandes, Karina Gonzalez Camara (2021)
In the clinical practice of dentistry, it is evident that despite advances in the area of ​​endodontics, microbial agents and technical errors are the main factors responsible for endodontic failure. The mechanical chemical preparation aims to remove necrotic, vital tissue, microorganismos and their by-products from the root canal system. However, this preparation is not sufficient for satisfactory cleaning due to the anatomical complexity of the root canal system, which can generate the permanence of microorganisms that may remain viable and active, interfering in the repair process of periradicular tissues. Thus, it is necessary to search for ideal irrigating chemical solutions that can provide better results in endodontic treatment. Within this context, the objective of this study is to provide, through a narrative review, an understanding of the current available evidence on the importance of using ozone O3, as an adjunct to irrigation of the root canal system in endodontic therapy. The research carried out characterizes as exploratory-descriptive, in terms of the approach, it consists of a qualitative research. The searches were carried out in the bibliographic databases of PubMed / MEDLINE, Virtual Health Library (VHL), Web of Science and SciELO. In this study, they state that ozone is capable of inactivating microorganisms through the direct oxidation of its structural components, and can be proposed as an adjunct in endodontic treatments against microorganisms (Gram positive and Gram negative) present in the oral cavity and root canals. If necessary, controlled and randomized clinical trials to endorse its efficacy and dosimetry in prevention and endodontic treatments.